Facile fabrication of RGO-WO3 composites for effective visible light photocatalytic degradation of sulfamethoxazole - Zhu, Wenyu; Sun, Faqian; Goei, Ronn; Zhou, Yan (Applied catalysis. B, Environmental, 2017)
[Display omitted] •RGO-WO3 composites were synthesized as visible light driven photocatalysts.•Increased sulfamethoxazole degradation efficiency was achieved by RGO-WO3.•Photocatalytic mechanism of sulfamethoxazole was investigated.•RGO-WO3 can be used in practical application to degrade organic pollutants. The presence of various antibiotics in the aquatic systems has become one of the emerging environmental issues. Sulfonamides group is one of the most commonly used antibiotics which cannot be effectively removed by conventional treatment methods. This study aims to explore the degradation feasibility of sulfonamides by applying novel photocatalysts powered by visible light. Sulfamethoxazole (SMX), one of the most widely used sulfonamide class antibiotics was chosen as target pollutant to evaluate the photocatalytic degradation performance. Three types of reduced graphene oxide-WO3 (RGO-WO3) composites (RW-100, RW-200 and RW-400) as visible light driven photocatalysts were prepared via a facile one step hydrothermal method. Without pH adjustment, more than 98% removal of SMX was achieved within 3 hours by both RW-200 and RW-100 under visible light irradiation. The good photocatalytic activity of RGO-WO3 composites demonstrates that they can be utilized as effective photocatalysts to degrade sulfonamide class of antibiotics. In addition, the photocatalytic intermediates of SMX were analyzed and the photodegradation pathway was proposed. RW-200 can be used for real application due to its high photocatalytic efficiency and excellent recyclability.